Vibrational power flow in beam-plate structures Part II: Beam-plate structure with isolating components - Yi, Chuijie; Dietz, Peter; Hu, Xuanli (Computer Assisted Methods in Engineering and Science, 1998)
The expressions of vibration power flow (VPF) in beam-plate structures (BPS) have been derived in the Part I of this paper. Based on those results got in Part I, Part II presents the expressions of VPF in BPS under the following three cases as shown Figs. 1,2 and 3 below. (1) the isolating component 1 (IC1) being added at the free end of the beam; (2) isolating component 2 (IC2) being embedded between the beam and the plate; and (:3) IC1 and IC2 being in BPS simultaneously (IC1 and IC2). According to these expressions, the corresponding numerical calculations are completed. The influence of parameter of the isolating components on VPF is also considered in this part. And then numerical calculations of VPF are verified by the measurements of VPF. Some valuable conclusions have been applied to vibration control of tracked vehicles mentioned in Part I.